2006
DOI: 10.1074/jbc.m510303200
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Mitochondria Are More Susceptible to Ca2+Overload than Nonsynaptic Mitochondria

Abstract: Mitochondria in nerve terminals are subjected to extensive Ca 2؉ fluxes and high energy demands, but the extent to which the synaptic mitochondria buffer Ca 2؉ is unclear. In this study, we identified a difference in the Ca 2؉ clearance ability of nonsynaptic versus synaptic mitochondrial populations enriched from rat cerebral cortex. Mitochondria were isolated using Percoll discontinuous gradients in combination with high pressure nitrogen cell disruption. Mitochondria in the nonsynaptic fraction originate fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
236
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(251 citation statements)
references
References 82 publications
(76 reference statements)
12
236
2
1
Order By: Relevance
“…S2) suggests that mitochondria play an important role in ADDLinduced oxidative stress. In this regard, mitochondria are known to accumulate in synapses (51,52), and a very recent study has shown that mitochondrial trafficking to synapses is dynamic and regulated by synaptic activity (53). Of considerable interest, that study also showed that mitochondria in dendritic synapses undergo marked morphological remodeling in neurons subjected to a neurotoxic glutamate insult (53).…”
Section: Discussionmentioning
confidence: 99%
“…S2) suggests that mitochondria play an important role in ADDLinduced oxidative stress. In this regard, mitochondria are known to accumulate in synapses (51,52), and a very recent study has shown that mitochondrial trafficking to synapses is dynamic and regulated by synaptic activity (53). Of considerable interest, that study also showed that mitochondria in dendritic synapses undergo marked morphological remodeling in neurons subjected to a neurotoxic glutamate insult (53).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that synaptic mitochondria are more susceptible to Ca 2+ overload than nonsynaptic mitochondria (Brown et al, 2006). Accordingly, Du and colleagues (2010) identified differences in synaptic versus nonsynaptic mitochondrial properties and function of mitochondrial populations isolated from AD transgenic mice brain overexpressing the human mutant form of APP and Aβ (Du et al, 2010).…”
Section: Synaptic Dysfunction In Admentioning
confidence: 99%
“…The respiratory activity of isolated mitochondria was measured using an oxygen monitor (Oxygraph, Hansatech Instruments, UK) equipped with a Clark-type oxygen electrode following the method of Brown et al (2006). Protein (100 μg) isolated from brain mitochondria was suspended in a sealed, constantly stirred, and thermostatically controlled chamber at 37°C in 2 ml of KCl respiration buffer [125 mM KCl, 0.1% (w/v) bovine serum albumin, 20 mM HEPES, 2 mM MgCl 2 , and 2.5 mM KH 2 PO 4 , pH 7.2].…”
Section: Measurement Of Mitochondrial Respirationmentioning
confidence: 99%
“…Following inhibition of ATP synthase by oligomycinA, the rate of oxygen consumption was minimized (State IV). RCR is defined as the ratio of the oxygen consumption rate for state III over state IV and has been widely used as an indicator of functional and structural integrity of isolated mitochondria (Brown et al, 2006). In general, mitochondria preparations with a RCR value higher Fig.…”
Section: Functionality and Purity Of Isolated Brain Mitochondriamentioning
confidence: 99%